Quality of life (QOL) among chronic kidney disease (CKD) patients in Hospital Universiti Sains Malaysia (HUSM) - Mohan, Ranjeni (Universiti Sains Malaysia, 2023)
CKD leads to decreased QoL by increasing the risk of death during the progression of its pathogenesis. However, many factors can be improved to support QOL. A cross-sectional study was conducted on 73 participants. A self-administered questionnaire was given to the participants that fit the inclusion criteria via face to face. A validated questionnaire and the kidney disease quality of life short form (KDQOLSF ™ 1.3) were used to assess QoL. The general objective of this study is to study the QoL among CKD patients in Hospital USM. They were selected through a nonprobability convenience sampling method. Data collected were statistically analyzed using Statistical Package Social Science (SPSS) software version of 26. A total of 73 participants were recruited into the study: were females (56.2%), married (89.0%), studied secondary (69.9%), unemployed (53.4%), with household income in the range of RM2000 – RM 3000 (35.6%), and village residents (63.0%). The mean score QoL among CKD in the domains of the PCS, MCS, and KDCS with and without hemodialysis were 1435.96 (SD 338.07), 1172.33 (SD 181.39), 3422.31 (SD 334.93) and 3526.23 (SD 259.09) respectively. The prevalence of good QoL among CKD in the domains of the PCS, MCS, and KDCS with and without hemodialysis were 20.5%, 16.4%, 15.4% and 16.7% respectively. Correlation between PCS and MCS shows slightly positive correlation and significant at p= 0.000 (p ≤0.01). After controlling for all potential confounding factors, two variables were found to be associated with QoL in the domains of PCS: age, and occupational status. Three variables were associated with QoL in the domain of MCS: age, marital status and occupational status. However, none of variables were significant to KDCS with and without hemodialysis. The level of QoL among CKD patients showed moderate in all domains. Montioring QoL is an important indicator to identify impact of CKD on PCS, MCS and KDCS domains. So, there is need for the healthcare system to develop an appropriate evidence based practice guideline for the assessmet and management for CKD patients.